1999
DOI: 10.1111/j.1469-7793.1999.687ad.x
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic factor, calpastatin and ATP together reverse run‐down of Ca2+ channel activity in guinea‐pig heart

Abstract: The cytoplasmic extract of bovine heart was separated into four fractions by gel filtration: H (molecular mass > 300 kDa), P (250‐300 kDa), L1 (180‐250 kDa) and L2 (< 180 kDa). The effects of these fractions on the run‐down of L‐type Ca2+ channel activity were investigated in guinea‐pig ventricular myocytes. After run‐down induced by inside‐out patch formation, Ca2+ channel activity was restored by P or H (+ 3 mM ATP) to 7·5 and 5·8 % of that in the cell‐attached mode, respectively, but to as high as 86 % by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 39 publications
2
36
0
Order By: Relevance
“…Adult guinea-pig ventricular myocytes were dispersed by collagenase and protease dissociation as described previously (27). Briefly, a female guinea pig (weight, 300 -500 g) was anesthetized with pentobarbital sodium (30 mg/kg, i.p.…”
Section: Preparation Of Single Cardiac Myocytesmentioning
confidence: 99%
“…Adult guinea-pig ventricular myocytes were dispersed by collagenase and protease dissociation as described previously (27). Briefly, a female guinea pig (weight, 300 -500 g) was anesthetized with pentobarbital sodium (30 mg/kg, i.p.…”
Section: Preparation Of Single Cardiac Myocytesmentioning
confidence: 99%
“…This phenomenon is referred to as rundown and can be considered as a failure of the mechanism by which the basal activity of the channel is maintained (1,2). So far, several mechanisms have been proposed for the run-down of Ca 2+ channels, including dephosphorylation of protein kinase A (PKA)-mediated phosphorylation (3) and proteolysis induced by calpain, a Ca…”
Section: Introductionmentioning
confidence: 99%
“…A previous report suggested that CS-induced recovery of Ca 2+ channel activity after run-down is related to the C-terminal region of the Cav1.2 channel, which includes the PreIQ and IQ motifs [2][3][4]14]. Therefore, binding of CS L with IQ and PreIQ may be one of the mechanisms required to maintain the basal activity of the Ca 2+ channel.…”
Section: Discussionmentioning
confidence: 99%
“…Wash-out of regulatory factors has been suggested as the primary mechanism responsible for the run-down of the L-type Ca 2+ channel [2][3][4]. A previous report suggested that CS-induced recovery of Ca 2+ channel activity after run-down is related to the C-terminal region of the Cav1.2 channel, which includes the PreIQ and IQ motifs [2][3][4]14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation